Study of bone marrow microstructure in healthy young adults using intravoxel incoherent motion diffusion-weighted MRI - Wu, Wenqi; Gong, Tong; Niu, Jinliang; Li, Wenjin; Li, Jianting; Song, Xiaoli; Cui, Sha; Bian, Wenjin; Wang, Jun (Frontiers in Endocrinology, 2022)
Bone marrow is the fourth largest organ of the human body. Assessing the microstructure of marrow and investigating the gender-related cellular and capillary network in marrow of healthy young adults could be helpful in understanding the process of bone metabolism. Intravoxel incoherent motion (IVIM) provides both diffusion and perfusion quantification without the need for intravenous contrast injection. In this prospective study, 60 healthy young age-matched volunteers (30 males and 30 females) underwent MRI scans at 1.5T using multi-b value (b= 0, 10, 25, 50, 100, 200, 400, 600, 800, 1000, 1200s/mm2) diffusion weighted imaging on sagittal planes covering the lumbar bone marrow. And apparent diffusion coefficient (ADC), true ADC (D), pseudo ADC (D*), and perfusion fraction (f) were calculated from diffusion weighted images by using the mono-exponential model and bi-exponential model. Regions of interests (ROIs) were selected centrally in the lumbar vertebral cancellous bone (L2–L4). An independent t-test was performed to detect significant difference in the ADC value and parameters of IVIM between males and females. Comparison of the parameters of IVIM in L2, L3 and L4 vertebras made using analysis of variance (ANOVA). P< 0.05 was considered to indicate a significant difference. The D value (0.28±0.04)×10-3mm2/s of females was significantly higher than that (0.20±0.04)×10-3mm2/s of males. The f was significantly higher in females (31.70±3.65)%compared with males (28.94±5.52)%.However, D* was significantly lower in females (46.72±12.90)×10-3mm2/s than that (91.78±30.83)×10-3mm2/s in males. And there was no significant difference between female and males in the conventional ADC value. Further, there were no significant difference of D, f and D* value among second, third and fourth lumbar vertebras of females. And there were no significant difference of these parameters in males either. IVIM parameters can discriminate marrow in younger females from males. It may provide noninvasive methods for evaluating the microstructure (cellularity and perfusion) of marrow.